BEBERAPA JENIS ROTAN DI GUNUNG CAKRABUANA, SUMEDANG, JAWA BARAT - Witono, Joko R; Daradjat, Tatang; Sujahman, Samsu (BERITA BIOLOGI, 2003)
Mount Cakrabuana in West Java possesses high plant diversity. Administratively, it is belong to Sumedang, Tasikmalaya, Garut,Majalengka, and Ciamis Regencies, The largest area is Sumedang (1.284,62 ha). There are 3 species of rattans found in the mountain Plectocomia elongate Mart, ex Bl., Calamus heteroideus Bl., and C. javensis Bl. Description, habitat, and the usage of the rattans is discussed.